Improving Emergency Preparedness System Readiness through Simulation and Interprofessional Education - Miller, Jane Lindsay (Association of Schools of Public Health, 2014)
We applied emerging evidence in simulation science to create a curriculum in emergency response for health science students and professionals. Our research project was designed to (1) test the effectiveness of specific immersive simulations, (2) create reliable assessment tools for emergency response and team communication skills, and (3) assess participants' retention and transfer of skills over time. We collected both quantitative and qualitative data about individual and team knowledge, skills, and attitudes. Content experts designed and pilot-tested scaled quantitative tools. Qualitative evaluations administered immediately after simulations and longitudinal surveys administered 6–12 months later measured student participants' individual perceptions of their confidence, readiness for emergency response, and transfer of skills to their day-to-day experience. Results from 312 participants enrolled in nine workshops during a 24-month period indicated that the 10-hour curriculum is efficient (compared with larger-scale or longer training programs) and effective in improving skills. The curriculum may be useful for public health practitioners interested in addressing public health emergency preparedness competencies and Institute of Medicine research priority areas.